World Intellectual Property Report 2022 : the direction of innovation. (World Intellectual Property Report (WIPR),, 2022)
What is the direction of innovation? As the world looks to rebuild from the pandemic, innovation has a crucial role to play in opening up new growth possibilities and creating much needed solutions to the common challenges we face. Decisions on innovation may be complex, but, as this report highlights, it is vital that they are understood.